Selecting KRI for Continuous Auditing: A Delphi Study - Silva, J.; Miklos A. Vasarhelyi; Laureano, Raul M. S. (66th World Continuous Auditing and Reporting Symposium, 2025)
The paper explores the selection of Key Risk Indicators (KRIs) for the continuous audit of service station operations using the Delphi method. Continuous auditing enhances risk management by leveraging real-time data to improve operational efficiency and organizational integrity. The study reviews the theoretical framework of continuous auditing and emphasizes the critical role of KRIs in modern risk assessment. Expert opinions were gathered to prioritize 13 relevant KRIs across four key areas: Operations, Stock Management, System Integration, and Cash Management, focusing on the specific context of service stations in the Iberian region. The findings reveal a shift from traditional periodic audits to a dynamic continuous model, enabling prompt detection of anomalies and informed decision-making. This research provides a structured approach to selecting effective KRIs, ultimately enhancing risk management processes and competitive advantage for organizations.